Ibn Sina's Spiritual Quotient as a Burnout Gen Z Solution: Analysis of Surah Al-Baqarah Verse 269 - Putri Rahayuningtyas Sativara; Yeti Dahliana (Jurnal test, 2026)
Burnout is a psychological syndrome characterized by physical and emotional exhaustion, depersonalization, and decreased self-efficacy. Currently, burnout among Indonesian society is experienced by 23.3% of Gen Z due to academic demands, social expectations, and digital media pressures that trigger a crisis of meaning in life. This qualitative research based on literature studies aims to analyze Ibn Sina's spiritual intelligence as a solution, with the novelty of synthesizing the philosophy of the soul and the theological foundation of Surah Al-Baqarah verse 269. Using a psychological approach and descriptive-interpretive analysis of primary sources in the form of the Qur'an and the Book of Al-Qanun fii Al-Tiibb. The study results in burnout as a form of holistic imbalance between the soul (al-nafs) and body (al-jism) which clinically resembles melancholic burnout (malankholia). This condition is caused by the failure of the human soul in controlling the balance of the vegetable soul and the animal soul, so that Ibn Sina's spiritual intelligence solution is focused on achieving al-hikmah (wisdom), through the human soul optimized by al-quwwah nazariyyah and al-quwwah amaliyyah to reach the highest level of reason (al-aql al-mustafad). This solution is oriented towards finding the meaning of life to face the challenges of the digital era, material happiness standards, and other social demands through four approaches: awareness of reason, soul management, mindfulness, and spiritual awareness.